Simultaneous Improvement of Yield Strength and Ductility at Cryogenic Temperature by Gradient Structure in 304 Stainless Steel - Shuang Qin; Muxin Yang; Fuping Yuan; Xiaolei Wu (Nanomaterials, 2021)
The tensile properties and the corresponding deformation mechanism of the graded 304 stainless steel (ss) at both room and cryogenic temperatures were investigated and compared with those of the coarse-grained (CGed) 304 ss. Gradient structures were found to have excellent synergy of strength and ductility at room temperature, and both the yield strength and the uniform elongation were found to be simultaneously improved at cryogenic temperature in the gradient structures, as compared to those for the CG sample. The hetero-deformation-induced (HDI) hardening was found to play a more important role in the gradient structures as compared to the CG sample and be more obvious at cryogenic temperature as compared to that at room temperature. The central layer in the gradient structures provides stronger strain hardening during tensile deformation at both temperatures, due to more volume fraction of martensitic transformation. The volume fraction of martensitic transformation in the gradient structures was found to be much higher at cryogenic temperature, resulting in a much stronger strain hardening at cryogenic temperature. The amount of martensitic transformation at the central layer of the gradient structures is observed to be even higher than that for the CG sample at cryogenic temperature, which is one of the origins for the simultaneous improvement of strength and ductility by the gradient structures at cryogenic temperature.